2020
DOI: 10.1177/1178638820903295
|View full text |Cite
|
Sign up to set email alerts
|

Is Energy Delivery Guided by Indirect Calorimetry Associated With Improved Clinical Outcomes in Critically Ill Patients? A Systematic Review and Meta-analysis

Abstract: Background: Indirect calorimetry (IC) is recommended to guide energy delivery over predictive equations in critical illness due to its precision. However, the impact of using IC to measure energy expenditure on clinical outcomes is uncertain. Objective: To evaluate whether using IC to measure energy expenditure to inform energy delivery reduced hospital mortality and improved other important outcomes compared to using predictive equations in critically ill adults. Methods: A systematic literature review was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
21
2
1
Order By: Relevance
“…In this updated meta-analysis, we found a better prognosis in the IC-guided group patients. This nding contrasts with a most recent meta-analysis by Tatucu-Babet and colleagues [11]. They reported an IC-guided energy delivery regimen showed no between-groups difference regarding mortality (both hospital and ICU mortality) and ICU LOS but a longer duration of MV.…”
Section: Discussioncontrasting
confidence: 56%
“…In this updated meta-analysis, we found a better prognosis in the IC-guided group patients. This nding contrasts with a most recent meta-analysis by Tatucu-Babet and colleagues [11]. They reported an IC-guided energy delivery regimen showed no between-groups difference regarding mortality (both hospital and ICU mortality) and ICU LOS but a longer duration of MV.…”
Section: Discussioncontrasting
confidence: 56%
“…A published meta-analysis showed that compared with predictive equations, the IC-guided energy delivery strategy was not more effective in reducing hospital mortality, duration of MV, and length of stay (LOS) in ICU or hospital [ 11 ]. However, only four studies have been included.…”
Section: Introductionmentioning
confidence: 99%
“…Despite guideline recommendations to use IC in critically ill patients, the superiority of IC-guided nutritional therapy has not yet been unequivocally proven in randomized clinical trials [ 15 , 86 , 99 ]. Even though it was confirmed that IC-guided nutrition support improves a patient’s nutritional status, the only significant benefit to outcome proven by RCTs is a significant decrease of nosocomial infections [ 46 , 100 102 ].…”
Section: Ic-guided Nutritionmentioning
confidence: 99%
“…All taken into account, the association of IC use with important clinical outcomes needs to be further explored before definitive conclusions about its use in the intensive care unit can be drawn. A recent systematic review and meta-analysis by Tatucu-Babet et al [ 99 ] identified 4060 articles on the effect of IC-guided nutrition and clinical outcomes and found only 4 single-center, randomized controlled trials with 396 patients included in the analysis. All 4 studies reported higher receipt of energy close to the measured energy expenditure by IC compared to the predictive equation arm.…”
Section: Ic-guided Nutritionmentioning
confidence: 99%